2013
DOI: 10.1146/annurev-immunol-020711-074950
|View full text |Cite
|
Sign up to set email alerts
|

The Dendritic Cell Lineage: Ontogeny and Function of Dendritic Cells and Their Subsets in the Steady State and the Inflamed Setting

Abstract: Dendritic cells (DCs) form a remarkable cellular network that shapes adaptive immune responses according to peripheral cues. After four decades of research, we now know that DCs arise from a hematopoietic lineage distinct from other leukocytes, establishing the DC system as a unique hematopoietic branch. Recent work has also established that tissue DCs consist of developmentally and functionally distinct subsets that differentially regulate T lymphocyte function. This review discusses major advances in our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
2,094
5
50

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,942 publications
(2,250 citation statements)
references
References 298 publications
31
2,094
5
50
Order By: Relevance
“…36 Thus, it will be interesting to dissect the differentiation fate and functionality of the Ly6C hi monocytes that were recruited by supernatants of irradiated tumor cells in our model in greater detail, for instance if they – in the course of differentiation – give rise to the Ly6C lo monocytic population which appeared in the air pouches, or if these cells rather are of tissue-resident origin. 52 …”
Section: Discussionmentioning
confidence: 99%
“…36 Thus, it will be interesting to dissect the differentiation fate and functionality of the Ly6C hi monocytes that were recruited by supernatants of irradiated tumor cells in our model in greater detail, for instance if they – in the course of differentiation – give rise to the Ly6C lo monocytic population which appeared in the air pouches, or if these cells rather are of tissue-resident origin. 52 …”
Section: Discussionmentioning
confidence: 99%
“…In the blood, human DC include lineage-negative (LIN-) HLA-DR+CD14-CD11c-CD123+ plasmacytoid DC and LIN-HLA-DR+CD14-CD11c+ conventional DC subsets, of which the latter can be subdivided into four different DC subsets (DC1 to DC4) based on the additional markers CLEC9A, CD141, CD1c, CD16, CD36, CD32b and CD163. 23 , 28 Blood analysis of six EOC patients and four healthy donors revealed that the HLA-DR+CD14-CD11c+ DC subset was mainly composed of CD141+CLEC9A+ DC1, CD1c+CD32b+ DC2, CD1 c+CD32b-CD36+CD163+ DC3 and CD1c-CD16+ DC4 subsets ( Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). The great majority of ‘professional’ DC in vivo derive from bone marrow pre‐DC 1. In this regard, studies addressing the effects of VD3 on murine DC have mostly cultured whole bone marrow with GM‐CSF or GM‐SCF + IL‐4 to generate CD11c + cells (GM‐CSF‐DC).…”
Section: Vd3 and DC Precursor (Pre‐dc) Derived Dc In The Mousementioning
confidence: 99%
“…CDP‐derived precursors exhibit early specialization to gut‐tropic mucosal DC precursors (pre‐μDC), regulated by retinoic acid (RA)6, 49 and classical DC precursors (pre‐cDC), and within the latter into cDC1 or cDC2 lineages in the bone marrow 80. Pre‐cDC and pre‐μDC then circulate through blood and home to tissues where they complete their differentiation under tissue‐specific influences 1, 6, 38, 49. The cMoP differentiate to human CD14 + /mouse Ly6C + monocytes and circulate through blood.…”
Section: Vd3 and DC Precursor (Pre‐dc) Derived Dc In The Mousementioning
confidence: 99%
See 1 more Smart Citation